(untitled) (Research, Society and Development, 2019)
Infrastructure is part of significant importance in the teaching-learning process of an educational institution by virtue of providing the necessary support for the full performance of academic and administrative functions as well as providing satisfaction for the student and society in general. In this context the present article seeks to analyze the perception of the students of the Federal Institute of Paraíba - IFPB Campus Guarabira, about the infrastructure that the Campus offers. For this purpose, a questionnaire with 39 questions was elaborated based on the authors Pieri and Santos, (2014), containing aspects of existence or not of the infrastructure items. The research universe is composed of 528 students who were regularly enrolled. A simple random sampling with 95% confidence level and 5% error was performed, totaling a sample with 168 participants, where it was possible to observe that the items surveyed are within one expected quality for students, however, it was also observed that there is an urgent need to improve some of the items aimed at the full development of student life.